Evaluating the effect of silicon liner on quality of gait in Transtibial amputees: A review of literature - Mostafa Kamali Ardakani; Tahmoureth Tahmasebi (Vesnu Publications, 2013)
Introduction: Lower limb amputations are usually performed in people suffering from trauma, vascular diseases, diabetes and/or congenital disorders. Amputees lose their ability to stand and walk depending to the level of amputation. Various types of prostheses can be used to improve the performance of amputees. The efficacy of lower-limb prosthesis is determined by the suitability of suspension method. In fact, using an appropriate fitting and suspension method plays an important role in the quality performance of prosthesis and patients' comfort when using prosthesis. Although three decade shave passed since the advent of silicone liner prostheses, the effect of this prosthetic system on the performance of silicone liner prostheses has not been yet clearly determined. Moreover, the effect of silicone liner on such parameters as speed of walking, standing stability and gait confidence is not cleared. Therefore, the aim of this review was to clarify the effect of silicone liner on abovementioned parameters based on the available literature. Materials and Methods: An electronic search was done via the PubMed, Embase and ISI web of knowledge databases from 1960 to 2012. The quality of papers was assessed using the Down and Black evaluation tool. Following keywords were used: silicone liner, Icelandic roll on silicon socket (ICEROSS), trans-tibial amputation, and trans-tibial prosthesis. Results: Based Based on the used keywords, 100 papers were found from which 10 papers were selected in accordance with the selection criteria. The scores of reporting, external validity, internal validity (bias), and internal validity (confounding) varied between 5-9, 1-3, 3-4, and 3-5, respectively. Conclusion: The results confirmed that this new system is better than the convention alone. It is worth mentioning that, no significant difference shave been found in quality of gait. Totally, we can say that more researches, such as clinical trials, are needed to understand the benefits of silicone prosthesis for below- knee amputees. Keywords: Silicon liner, Lower limb prosthesis, Lower limb amputation